1997
DOI: 10.1016/s0092-8674(00)80300-1
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Ethylene Gas Response Pathway in Arabidopsis by the Nuclear Protein ETHYLENE-INSENSITIVE3 and Related Proteins

Abstract: Mutations in the Arabidopsis ETHYLENE-INSENSITIVE3 (EIN3) gene severely limit a plant's response to the gaseous hormone ethylene. ein3 mutants show a loss of ethylene-mediated effects including gene expression, the triple response, cell growth inhibition, and accelerated senescence. EIN3 acts downstream of the histidine kinase ethylene receptor, ETR1, and the Raf-like kinase, CTR1. The EIN3 gene encodes a novel nuclear-localized protein that shares sequence similarity, structural features, and genetic function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
843
0
11

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 900 publications
(876 citation statements)
references
References 55 publications
22
843
0
11
Order By: Relevance
“…The ethylene signal is transduced to ETHYLENE INSEN-SITIVE3 (EIN3) through CONSTITUTIVE TRIPLE RE-SPONSE1 (CTR1) (Kieber et al 1993) and ETHYLENE INSENSITIVE2 (EIN2) (Alonso et al 1999). EIN3 is a transcription factor that plays a crucial role in regulation of expression of ethylene responsive genes (Chao et al 1997;Solano et al 1998). Studies have also revealed that in absence of ethylene EIN3 protein is quickly degraded through a ubiquitin-proteasome pathway mediated by two F-box proteins, [EIN3-binding F box protein 1 and 2 (EBF1 and EBF2)] whereas EIN3 protein is stabilized by ethylene itself (Guo and Ecker 2003;Potuschak et al 2003;Gagne et al 2004).…”
Section: Role Of Ethylene In Regulation Of Fruit Ripeningmentioning
confidence: 99%
“…The ethylene signal is transduced to ETHYLENE INSEN-SITIVE3 (EIN3) through CONSTITUTIVE TRIPLE RE-SPONSE1 (CTR1) (Kieber et al 1993) and ETHYLENE INSENSITIVE2 (EIN2) (Alonso et al 1999). EIN3 is a transcription factor that plays a crucial role in regulation of expression of ethylene responsive genes (Chao et al 1997;Solano et al 1998). Studies have also revealed that in absence of ethylene EIN3 protein is quickly degraded through a ubiquitin-proteasome pathway mediated by two F-box proteins, [EIN3-binding F box protein 1 and 2 (EBF1 and EBF2)] whereas EIN3 protein is stabilized by ethylene itself (Guo and Ecker 2003;Potuschak et al 2003;Gagne et al 2004).…”
Section: Role Of Ethylene In Regulation Of Fruit Ripeningmentioning
confidence: 99%
“…EIN2 was reported to localize at the ER membrane when transiently expressed in tobacco leaf cells [4]. EIN3 (ETHYLENE INSENSITIVE3) and its homolog EIL1 (EIN3-LIKE1) are two nuclear-localized transcription factors genetically acting downstream of EIN2 [5,6]. However, it remains a long mystery on how the ethylene signal is transmitted from ER-located EIN2 into the nucleus to modulate EIN3/EIL1-directed transcription.…”
mentioning
confidence: 99%
“…We hypothesized that HOS1 is associated with ethylene signaling, because the hos1-3 mutant showed similar phenotypes in leaf expansion to the ctr1 mutant that exhibits constitutive ethylene responses. 14 To investigate whether alterations in ethylene signaling underlie reduced leaf expansion of hos1-3, we employed a chemical inhibitor of ethylene receptors, STS. The ethylene receptors require the copper ion for high-affinity ethylene binding.…”
mentioning
confidence: 99%